If you would like to divide 3 and 1/6/(-9), you can do it using the following steps:
3 / 1/6/(-9) = 3/1 / 1/6/(-9) = 3/1 * (-9)/1/6 = -27 / 1/6 = -27 * 6 = -162
The result you get is -162.
Answer:
it increase and by 16.7
Step-by-step explanation:
Well, the square root of 12 is 3.464101615
substitute 4 as x in both sides of the equation
basically multiply -3/2 by 4
Answer:
AB = 9/2 cm
AB = 4.5 cm
Step-by-step explanation:
The area of small rectangle
x * (x-4) = x^2 -4x
The area of the big rectangle
The height is 2x +x and the width is x-2
(2x+x) * (x-2)
(3x) * (x-2)
3x^2 -6x
Add the areas together
x^2 -4x + 3x^2 -6x
4x^2 -10x
This is equal to 36
4x^2 -10x=36
Subtract 36 from each side
4x^2 -10x -36=36-36
4x^2 -10x-36=0
Divide each side by 2
2x^2 -5x -18=0
Factor
(x + 2) (2 x - 9) = 0
Using the zero product property
x+2=0 2x-9=0
x = -2 2x =9
x = -2 x = 9/2
Since we cant have a negative length
x = 9/2
AB = 9/2 cm